The risk variant in ODZ4 for bipolar disorder impacts on amygdala activation during reward processing - Heinrich, Angela; Lourdusamy, Anbarasu; Tzschoppe, Jelka; Vollstädt-Klein, Sabine; Bühler, Mira; Steiner, Sabina; Bach, Christiane; Poustka, Luise; Banaschewski, Tobias; Barker, Gareth; Büchel, Christian; Conrod, Patricia; et al. (Bipolar disorders, 2013)
Objectives Bipolar disorder is a severe mood disorder, which normally begins during adolescence or early adulthood and has a heritability of up to 80%. The largest genome-wide association analysis of bipolar disorder recently identified a new genome-wide associated variant in OZD4 (rs12576775). The aim of the present study was to further elucidate the role of this risk variant in the disease process using an imaging genetics approach. As increased amygdala and striatal responses during the processing of reward and emotion are characteristic for bipolar disorder patients, it was tested whether the risk variant has an influence on this endophenotype in healthy adolescents. Methods We examined the impact of the risk variant rs12576775 on functional magnetic resonance imaging data in an adolescent sample (N = 485). Differential activation between carriers of the risk allele (G-allele) and homozygous A-allele carriers in the amygdala and the striatum during a modification of the monetary incentive delay task (examining reward) and a face task (examining emotion) was analyzed. Results Carriers of the risk allele showed an increased blood oxygen level-dependent response in the amygdala during reward sensitivity (p = 0.05) and reward expectation (p < 0.05) but not during the face task. No significant group differences were found in the striatum during both reward and emotion processing. Conclusion Our results indicate that the ODZ4 risk variant influences reward processing in the amygdala. Alterations in the processing of emotion may have different underlying mechanisms and need to be further examined.
Gesehen am 21.12.2021